Global Evidence on Economic Preferences - Anke Becker; Thomas Dohmen; Benjamin Enke; Armin Falk; David Huffman; Uwe Sunde (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
This paper studies the global variation in economic preferences. For this purpose, we present the Global Preference Survey (GPS), an experimentally validated survey dataset of time preference, risk preference, positive and negative reciprocity, altruism, and trust from 80,000 individuals in 76 countries. The data reveal substantial heterogeneity in preferences across countries, but even larger within-country heterogeneity. Across individuals, preferences vary with age, gender, and cognitive ability, yet these relationships appear partly country specific. At the country level, the data reveal correlations between preferences and bio-geographic and cultural variables such as agricultural suitability, language structure, and religion. Variation in preferences is also correlated with economic outcomes and behaviors. Within countries and subnational regions, preferences are linked to individual savings decisions, labor market choices, and prosocial behaviors. Across countries, preferences vary with aggregate outcomes ranging from per capita income, to entrepreneurial activities, to the frequency of armed conflicts.
Keywords: D01; D03; F00; 330